2017
DOI: 10.1186/s12970-017-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute pomegranate extract supplementation on oxygen uptake in highly-trained cyclists during high-intensity exercise in a high altitude environment

Abstract: BackgroundRecent research has indicated that pomegranate extract (POMx) may improve performance during aerobic exercise by enhancing the matching of vascular oxygen (O2) provision to muscular requirements. POMx is rich in ellagitannin polyphenols and nitrates (NO3 −), which are both associated with improvements in blood flow and O2 delivery. Primarily, this study aimed to determine whether POMx improves performance in a cycling time trial to exhaustion at 100%VO2max (TTE100%) in highly-trained cyclists. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…In contrast, a previous study has reported no improvement in 20-km TT performance in moderately trained individuals following MC supplementation despite a 3-day ingestion of dried Montmorency cherries which provided 216 mg of polyphenol of which the final dose was administered 2–3 h prior to the cycling trial (Clifford et al 2013). In addition, not all studies have found ergogenic effects of polyphenol ingestion (Crum et al 2017; Labonté et al 2013). The absence of effect in these studies may relate to differences in dosing (i.e., 462 vs. 216 mg; 7 vs. 3 days, Clifford et al 2013), training status (i.e., novice vs. athlete, Crum et al 2017; Labonté et al 2013), environmental conditions (i.e., high altitude, Crum et al 2017), current antioxidant status (i.e., high vs. low, Green et al 2004) as well as the timing of intake (i.e., 60 min vs. 2–3 h prior to exercise, Clifford et al 2013) which may have marked effects on the ergogenic effects of polyphenol supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a previous study has reported no improvement in 20-km TT performance in moderately trained individuals following MC supplementation despite a 3-day ingestion of dried Montmorency cherries which provided 216 mg of polyphenol of which the final dose was administered 2–3 h prior to the cycling trial (Clifford et al 2013). In addition, not all studies have found ergogenic effects of polyphenol ingestion (Crum et al 2017; Labonté et al 2013). The absence of effect in these studies may relate to differences in dosing (i.e., 462 vs. 216 mg; 7 vs. 3 days, Clifford et al 2013), training status (i.e., novice vs. athlete, Crum et al 2017; Labonté et al 2013), environmental conditions (i.e., high altitude, Crum et al 2017), current antioxidant status (i.e., high vs. low, Green et al 2004) as well as the timing of intake (i.e., 60 min vs. 2–3 h prior to exercise, Clifford et al 2013) which may have marked effects on the ergogenic effects of polyphenol supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, Lactobacillus plantarum TWK10 supplementation improved exercise performance according to Chen et al (27) . Studies of supplementation with pomegranate extract or pomegranate juice in humans submitted to high-intensity aerobic exercise showed a decrease of oxidative stress caused by exercise but did not show improvement in physical performance (15,39) .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary controls are a further factor worthy of consideration. Several of the reviewed studies incorporated some element of dietary polyphenol restriction [ 11 , 64 , 67 , 80 , 82 , 107 , 120 , 136 ], in attempts to reduce the background noise that may be introduced by variation in dietary polyphenol intake, but which may also maximise the effects produced by polyphenol supplementation. Habitual polyphenol intake is difficult to accurately quantify, since despite our knowledge that polyphenol content of foods will be highly variable, reliance on standard values is required ( http://phenol-explorer.eu/ is an excellent resource for this purpose).…”
Section: Methodological Limitations and Future Workmentioning
confidence: 99%
“…Consumption of 1 g of pomegranate extract [ 63 ] 30 min pre-exercise or a combined supplement of pomegranate, green tea and grape extract (290 mg polyphenols [ 66 ]) consumed 1 h pre-exercise enhanced time to exhaustion whilst running at 90 and 100% of peak velocity achieved at and peak and average power output during repeated cycle Wingate tests in recreationally active individuals, respectively. However, trained cyclists [ 64 ] and recreationally resistance-trained individuals [ 65 ] did not derive significant performance benefit from consumption of 1 g of pomegranate extract. Specifically, time to exhaustion at 100% workload was not enhanced by consumption of pomegranate 2.5 h pre-exercise either at sea level or at the equivalent of 1657 m altitude, despite a significant increase in oxygen consumption in the altitude condition after supplementation, and increased plasma nitrate concentration after pomegranate supplementation [ 64 ].…”
Section: Fruit-derived Polyphenols and Exercise Performancementioning
confidence: 99%
See 1 more Smart Citation